Judicial Reform and Democratic Consolidation in Indonesia - Ibnu Sina Chandranegara; Syaiful Bakhri; Muhammad Ali (Jurnal Cita Hukum, 2019)
AbstractConstitutional Reform after fall of Soeharto’s New Order bring favorable direction for judiciary. Constitutional guarantee of judicial independence as regulated in Art 24 (1) of the 1945 Constitution, closing dark memories in the past. In addition, in Art 24 (2) of the 1945 Constitution decide the Judiciary is held by the Supreme Court and the judicial bodies below and a Constitutional Court. Such a strict direction of regulation plus the transformation of the political system in a democratic direction should bring about the implementation of the independent and autonomous judiciary. But in reality, even though in a democratic political system and constitutional arrangement affirms the guarantee of independence, but it doesn’t represent the actual situation. There some problem which still remains, such as (i) the absence of a permanent format regarding the institutional relationship between the Supreme Court, the Constitutional Court and Judicial Commission, and (ii) still many efforts to weaken judiciary through many ways such criminalization of judge. Referring to the problem above, then there are gaps between what “is” and what “ought”, among others, First, by changes political configuration that tend to be more democratic, the judiciary should be more autonomous. But in reality, various problems arise such as (i) disharmony in regulating the pattern of relations between judicial power actors, (ii) various attempts to criminalize judges over their decisions, (iii) judicial corruption. Second, by the constitutional guarantee of the independence of the judiciary, there will be no legislation which reduced constitutional guarantee. But in reality, many legislation or regulations that still not in line with a constitutional guarantee concerning judicial independence. This paper reviews and describes in-depth about how to implement constitutional guarantees of judicial independence under democratic consolidation after fall of new order and conceptualize its order to strengthening rule of law in IndonesiaKeyword: Judicial Reform, Judicial Independence, Judicial Accountability, Democratic Consolidation AbstrakPerubahan UUD 1945 membawa arah yang menguntungkan bagi cabang kekuasaan kehakiman di Indonesia. Penjaminan kemerdekaan kekuasaan kehakiman sebagaimana diatur dalam Pasal 24 (1) UUD 1945 seperti menutup ingatan kelam di masa lalu. Selain itu, dalam Pasal 24 (2) UUD 1945 yang menentukan kekuasaan kehakiman dipegang oleh Mahkamah Agung dan badan-badan peradilan di bawahnya  dan Mahkamah Konstitusi. Dengan dasar ini, tidak ada landasan hukum sedikitpun bagi Presiden atau DPR untuk mengintervensi cabang kekuasaan kehakiman. Tetapi dalam kenyataannya, meskipun dalam sistem politik yang demokratis dan pengaturan konstitusional menegaskan jaminan kemerdekaan namun kenyataannya tidak mewakili situasi aktual. Terdapat beberapa masalah yang masih tersisa, seperti (i) tidak adanya format permanen mengenai hubungan kelembagaan antara Mahkamah Agung, Mahkamah Konstitusi dan Komisi Yudisial, (ii) masih banyak upaya untuk melemahkan peradilan melalui banyak cara kriminalisasi hakim. Mengacu pada masalah di atas, maka ada kesenjangan antara apa yang senyatanya dan apa yang seharusnya antara lain, Pertama, perubahan konfigurasi politik yang cenderung lebih demokratis, kekuasaan kehakiman harus lebih otonom. Namun dalam kenyataannya, berbagai masalah muncul seperti (i) ketidakharmonisan dalam mengatur pola hubungan antara aktor kekuasaan Kehakiman, (ii) berbagai upaya untuk mengkriminalkan hakim atas keputusan mereka, (iii) berkembangnya praktek mafia peradilan. Kedua, dengan jaminan kemerdekaan kekuasaan kehakiman, seharusnya tidak akan ada undang-undang yang mengurangi jaminan kemerdekaan kekuasaan kehakiman. Namun pada kenyataannya, banyak peraturan perundang-undangan yang masih belum sejalan dengan jaminan konstitusional mengenai kemerdekaan kekuasaan kehakiman. Makalah ini bermaksud menguraikan secara mendalam tentang bagaimana menerapkan jaminan konstitusional atas kemerdekaan kekuasaan kehakiman dalam masa konsolidasi demokrasi pasca jatuhnya orde baru dan mengkonseptualisasikan agenda reformasi peradilan untuk memperkuat supremasi hukum di IndonesiaKeyword: Reformasi peradilan, kemerdekaan kekuasaan kehakiman, reformasi peradilan, konsolidasi reformasi АннотацияКонституционная реформа после падения Нового Порядка (New Order) Сухарто дала благоприятное направление для судебной власти. Конституционная гарантия на независимость судебной власти, регулируемая статьей 24 (1) Конституции 1945 года, позволяет оставить мрачные воспоминания в прошлом. Кроме того, в статье 24 (2) Конституции 1945 года определено, что судебная власть находится в ведении Верховного Суда, нижестоящих судебных органов и Конституционного Суда. Такие строгие нормативные директивы в сочетании с трансформацией политической системы в демократическом направлении должны привести к созданию независимой и автономной судебной власти. Но на самом деле, хотя в демократической политической системе и конституционных механизмах закрепляется гарантия независимости, онa не отражает реальную ситуацию. Существует ряд нерешенных вопросов, таких как (i) отсутствие постоянного формата об институциональных отношениях между Верховным Судом, Конституционным Судом и Судебной Комиссией, и (ii) по-прежнему предпринимаются многочисленные попытки ослабить судебную власть многими средствами, такими как криминализация судей. Ссылаясь на вышеупомянутую проблему, существует разрыв между тем, что «есть» и что «должно быть», среди прочего: во-первых, изменяя политические конфигурации, которые имеют тенденцию быть более демократичными, судебная власть должна быть более автономной. Во-вторых, с конституционной гарантией на независимость судебной власти не будет закона, который ограничивал бы конституционные гарантии. В этой статье рассматривается и подробно объясняется, как реализовать конституционные гарантии независимости судебной власти после политического преобразования и концептуализировать его порядок для укрепления верховенства закона в Индонезии.Ключевые слова: независимость судебной власти, судебная ответственность, судебная реформа